Intercultural practicum: Perceptual learning through video in the pandemic context - Dawn Joseph; Richard Johnson (New Zealand Journal of Teachers' Work)
In our work with Australian initial teacher education (ITE) students our emphasis is on encouraging students to understand different cultural practices. Drawing on narrative reflection, we discuss intercultural and pedagogical concerns in which ITE students undertake international practicums. We recognise these students have a predominantly Western lens when undertaking practicums in Asian countries. To address this issue a video A Day in the Life… of Tamil School Children (https://youtu.be/vPdiogRR-Ig) in India was produced to change, improve and help students learn about the social and cultural environment of the ‘international student’. Students who took part in previous international practicums agreed that the video was an effective tool for cultural familiarisation. During this time of COVID-19 with travel restrictions abroad, the video resource serves as an effective visual pedagogy to build cultural understanding, embrace diversity, enable perceptual learning and empowering students to cultivate intercultural understandings of ‘the other’.